2020
DOI: 10.3389/fgene.2020.01002
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Immune-Related Prognostic Signature Associated With Immune Infiltration in Melanoma

Abstract: Melanoma is the leading cause of cancer-related death among skin tumors, with an increasing incidence worldwide. Few studies have effectively investigated the significance of an immune-related gene (IRG) signature for melanoma prognosis. Here, we constructed an IRGs prognostic signature using bioinformatics methods and evaluated and validated its predictive capability. Then, immune cell infiltration and tumor mutation burden (TMB) landscapes associated with this signature in melanoma were analyzed comprehensiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 35 publications
(42 reference statements)
1
13
0
Order By: Relevance
“…Liu et al. identified 10 DE IRGs between primary and metastatic melanoma, and investigated the immune infiltration and tumor mutation burden in different risk groups ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al. identified 10 DE IRGs between primary and metastatic melanoma, and investigated the immune infiltration and tumor mutation burden in different risk groups ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that enhanced local immune activation contributes to a good prognosis in different kind of tumors (25,26). In cutaneous melanoma, though several studies have reported that patients with high immune cell infiltration showed better prognosis (27)(28)(29), some types of immune cells are associated with worse prognosis, such as CD20-positive tumor-infiltrating lymphocytes, neutrophil granulocytes and mast cells (30,31). In our study, based on the immunogenomic profiling of 29 immune signatures, we found that Immunity_L group was associated with better prognosis, which might be the infiltrated immune cells are non-tumorspecific and do not show the anti-tumor effect.…”
Section: Discussionmentioning
confidence: 99%
“…However, the specific mechanism of how these genes influence T cell function remains elusive, it would be very interesting to further investigate into each of them in the following study. In this work, we found the combination of these six genes had a novel and good predictivity on melanoma patients, which performed better than the existing signature genes (Supplementary Figures 4, 5) (43,44,(49)(50)(51). Although the six gene signature in our work had a similar performance with the signature from Tian' s study for melanoma patients' survival, our signature had a better capability in predicting patients' response to immunotherapy (Figures 7H, K, Supplementary Figures 7A-C).…”
Section: Discussionmentioning
confidence: 74%
“…We further compared the predictiblibity of this signature with other previously developed immune-related signatures. Eleven studies were screened out after literature searching (42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52), but five signatures were not included for further analyses for at least one of the following reasons: lack of formula to calculate the risk score or immune-related score; lack of validation in extra datasets; lack of RNA expression data of some signature genes in validated datasets in the current work (45)(46)(47)(48)52). As reflected by the AUC values at 1-year, 3-year and 5-years in Supplementary Figures 4A-D and 5A-C, the signatures developed in our work and Tian's work had relatively better performance in predicting outcome of melanoma patients.…”
Section: A Representative Risk Score For Patient Survival Is Constructed Based On Six Signature Genesmentioning
confidence: 99%